2020
DOI: 10.1371/journal.pone.0237469
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic clustering networks among heterosexual migrants with new HIV diagnoses post-migration in Australia

Abstract: Background It is estimated that approximately half of new HIV diagnoses among heterosexual migrants in Victoria, Australia, were acquired post-migration. We investigated the characteristics of phylogenetic clusters in notified cases of HIV among heterosexual migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Of the 22 CRF01_AE clusters seven (32%) contained exclusively infections among individuals reporting a transmission risk other than MSM, with the largest of these clusters only containing four infections. Our finding is similar to that of a recent study from the state of Victoria, Australia, which found that heterosexual transmissions rarely lead to more than one new infection within that state [29]. Overall, we found nine active growing clusters for CRF01_AE, of which seven contained infections from notifications in 2018.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 22 CRF01_AE clusters seven (32%) contained exclusively infections among individuals reporting a transmission risk other than MSM, with the largest of these clusters only containing four infections. Our finding is similar to that of a recent study from the state of Victoria, Australia, which found that heterosexual transmissions rarely lead to more than one new infection within that state [29]. Overall, we found nine active growing clusters for CRF01_AE, of which seven contained infections from notifications in 2018.…”
Section: Discussionsupporting
confidence: 90%
“…Third, while CD4 count and VL data were used to approximate duration of HIV infection, determining the recency of infection using validated methods (e.g., genetic sequence diversity) [ 27 , 28 , 29 ] may have provided complimentary information to estimate the timing of HIV acquisition. Finally, social desirability bias may have impacted the reporting of sexual orientation, particularly among MSM [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, many using Bayesian methods, have shown significant post-migration HIV acquisition among certain migrant populations [ 2 , 8 , 9 , 10 ]. Timely HIV screening and linkage to care thus becomes particularly important for preventing both individual-level morbidity and mortality and onward transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, now is the time where a combined effort could lead to the virtual elimination of HIV transmission in Australia. Several efforts have been made towards this goal through institutional partnerships and funding such as the New South Wales HIV Prevention Partnership Project 2022–2026 ( Kirby, 2022 ), individual molecular epidemiological studies ( Di Giallonardo et al., 2019 ; Sacks-Davis et al., 2020 ; Pinto et al., 2018 ), the continuation of the needle and syringe program, Healthcare worker training, and the expansion of PrEP prescribers ( NSWH, 2020 ).…”
Section: Why Does Australia Need Molecular Epidemiology As a Pillar I...mentioning
confidence: 99%